Producción de carbón activado con raquis de banano y su efecto en el tratamiento de agua destinada al consumo humano, Quevedo año 2018 - Méndez Verduga, Ronny Antonio (2019)
In this work, activated carbon was synthesized from Musa Paradisiaca Cavendish rachis and was evaluated as an adsorbent of methylene blue and contaminants present in water from deep wells. It presents the optimal variables in particle size, carbonization temperature and carbonization time. Evaluating the quality of water for human consumption by calculating the ICA proposed by Brown and NSF, the efficiency of activated carbon was determined as a filter bed in the treatment of water from deep wells, which showed an increase in the water quality index with a classification equivalent to good. Keywords: Activated Carbon, Water Treatment.